Prenatal and Postnatal Sonographic Confirmation of Congenital Absence of the Ductus Venosus in a Child with Noonan Syndrome. (6th September 2017) - Newman, Christopher L.; Wanner, Matthew R.; Brown, Brandon P.
Abstract : The ductus venosus serves as an important vascular pathway for intrauterine circulation. This case presents a description of an absent ductus venosus in a female patient with Noonan syndrome, including both prenatal and postnatal imaging of the anomaly. In the setting of the anomalous vascular connection, the umbilical vein courses inferiorly to the iliac vein in parallel configuration with the umbilical artery. This finding was suspected based on prenatal imaging and the case was brought to attention when placement of an umbilical catheter was thought to be malpositioned given its appearance on radiography. Ultrasound imaging confirmed the anomalous course. This is in keeping with prior descriptions in the literature of an association between Noonan syndrome and aberrant umbilical venous drainage. This case illustrates the need for awareness of this condition by the radiologist, allowing for identification on radiographs and the recommendation for further confirmatory imaging. Further, the case illustrates the value of paying particular attention to the fetal course of the umbilical vessels in patients with suspected Noonan syndrome, as this population is particularly at risk for anomalous vasculature.